Prediction of University-Level Academic Performance through Machine Learning Mechanisms and Supervised Methods - Leonardo Emiro Contreras Bravo; Nayibe Nieves-Pimiento; Karolina Gonzalez-Guerrero (Ingeniería, 2022)
Context:  In the education sector, variables have been identified which considerably affect students’ academic performance. In the last decade, research has been carried out from various fields such as psychology, statistics, and data analytics in order to predict academic performance.